2017
DOI: 10.1002/kin.21101
|View full text |Cite
|
Sign up to set email alerts
|

An Estimation of the Levels of Stabilized Criegee Intermediates in the UK Urban and Rural Atmosphere Using the Steady-State Approximation and the Potential Effects of These Intermediates on Tropospheric Oxidation Cycles

Abstract: Levels of the stabilized Criegee Intermediate (sCI), produced via the ozonolysis of unsaturated volatile organic compounds (VOCs), were estimated at two London urban sites (Marylebone Road and Eltham) and one rural site (Harwell) in the UK over the period of 1998–2012. The steady‐state approximation was applied to data obtained from the NETCEN (National Environmental Technology Centre) database, and the levels of annual average sCI were estimated to be in the range of 30–3000 molecules cm−3 for UK sites. A con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 55 publications
1
31
0
Order By: Relevance
“…A limited number of olefins producing CH 3 COOH through Criegee intermediate, CH 3 CHOO formation, are used in the model because of the lack of their emission inventories. Khan, Morris, et al () found the most abundant Criegee to be CH 3 CHOO (73%) among all other Criegee Intermediates in the UK urban environment. The dominating precursors of CH 3 CHOO were found in their study to be 2‐methyl‐2‐butene (49%), trans‐2‐butene (17%), cis‐2‐butene (11%), trans‐2‐pentene (5%), propene (5%), cis‐2‐pentene (2%), 4‐methyl‐trans‐2‐pentene (2%), 3‐methyl‐trans‐2‐pentene (2%), 3‐methyl‐cis‐2‐pentene (3%), and trans‐2‐hexene (1%).…”
Section: Resultsmentioning
confidence: 99%
“…A limited number of olefins producing CH 3 COOH through Criegee intermediate, CH 3 CHOO formation, are used in the model because of the lack of their emission inventories. Khan, Morris, et al () found the most abundant Criegee to be CH 3 CHOO (73%) among all other Criegee Intermediates in the UK urban environment. The dominating precursors of CH 3 CHOO were found in their study to be 2‐methyl‐2‐butene (49%), trans‐2‐butene (17%), cis‐2‐butene (11%), trans‐2‐pentene (5%), propene (5%), cis‐2‐pentene (2%), 4‐methyl‐trans‐2‐pentene (2%), 3‐methyl‐trans‐2‐pentene (2%), 3‐methyl‐cis‐2‐pentene (3%), and trans‐2‐hexene (1%).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 7. The hourly, monthly, and daily estimated sCI concentrations in the two urban sites and one rural site of UK (Adapted from Khan et al 105 ). The error bars represents ± 1 SD of the whole data series.…”
Section: Estimation Of Regional and Globalmentioning
confidence: 99%
“…The modeling studies currently available in the literature [17][18][19][20][21][22]54,65 did not have access to sufficiently detailed information, and of necessity adopted identical rate coefficients for very diverse families of SCI, resulting in large uncertainties and large variations across the SCI concentration predictions. Based on the rate coefficients obtained above for unimolecular reactions and reaction with H 2 O and (H 2 O) 2 , combined with sitespecific ozonolysis rates from literature, and field measurement data [33][34][35][36] on the relevant VOC, O 3 , NO 2 , SO 2 , carboxylic acid, and H 2 O concentrations, the speciated steady-state SCI concentration can then be estimated.…”
Section: The Atmospheric Concentration and Speciation Of Scimentioning
confidence: 99%
“…The production rates and the contribution in the total SCI formation are given for sites with mostly biogenic emissions (Amazonia and Sierra Nevada combined), and for a site with mostly anthropogenic emission (Mexico city stark contrast to early estimates that predicted up to 800% increase in SO 2 oxidation in some regions, but are in line with more recent modeling estimates. 18,22 Further studies are needed to investigate the subsequent impact of SCI-induced H 2 SO 4 formation on the nucleation rates or aerosol chemistry in these regions. Fig.…”
Section: Impact Of Sci On Atmospheric Chemistrymentioning
confidence: 99%
See 1 more Smart Citation